A Computational Modeling Approach on Three‐Digit Number Processing. (4th March 2013) - Huber, Stefan; Moeller, Korbinian; Nuerk, Hans‐Christoph; Willmes, Klaus
Abstract Recent findings indicate that the constituting digits of multi‐digit numbers are processed, decomposed into units, tens, and so on, rather than integrated into one entity. This is suggested by interfering effects of unit digit processing on two‐digit number comparison. In the present study, we extended the computational model for two‐digit number magnitude comparison of Moeller, Huber, Nuerk, and Willmes (2011a) to the case of three‐digit number comparison (e.g., 371_826). In a second step, we evaluated how hundred‐decade and hundred‐unit compatibility effects were moderated by varying the percentage of within‐hundred (e.g., 539_582) and within‐hundred‐and‐decade filler items (e.g., 483_489). From the results we predict that numerical distance as well as compatibility effects should indeed be modulated by the relevance of tens and units in three‐digit number magnitude comparison: While in particular the hundred distance effect should decrease, we predict hundred‐decade and hundred‐unit compatibility effects to increase with the relevance of tens and units.